2013
DOI: 10.5296/ijele.v2i1.4650
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Emotional Intelligence and Willingness to Communicate among EFL Learners

Abstract: The primary goal of this investigation was to explore the existence of any possible relationship between willingness to communicate (WTC) and emotional intelligence (EI) among 60 EFL learners. The data for the research were gathered using WTC and EI questionnaires which were presented in the participants' native language. The modified version of likert-type WTC questionnaire developed by MacIntyre, Baker, Clement, and Conrod (2001) was employed to assess the participants' degree of WTC. Students' EI was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…Moreover, intrapersonal intelligence enables one to differentiate highly complex situations and feelings (Gardner, 1983). This finding is in congruence with findings of a study by Tabatabaei and Jamshidifar (2013) on the relationship between EFL students' EI and WTC The results of this study also indicated that interpersonal intelligence and WTC show stronger correlation than other EI variables. One justification for this result could be that understanding others and building a mutually satisfactory relationship with them could result in more WTC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, intrapersonal intelligence enables one to differentiate highly complex situations and feelings (Gardner, 1983). This finding is in congruence with findings of a study by Tabatabaei and Jamshidifar (2013) on the relationship between EFL students' EI and WTC The results of this study also indicated that interpersonal intelligence and WTC show stronger correlation than other EI variables. One justification for this result could be that understanding others and building a mutually satisfactory relationship with them could result in more WTC.…”
Section: Discussionsupporting
confidence: 91%
“…The results of their study revealed a significant association among EFL students' multiple intelligences (especially interpersonal intelligence) and their WTC and this association was affected by students' gender. Tabatabaei and Jamshidifar (2013) found a significant relationship between Iranian EFL learners' EI and their WTC at university level. However, other communication traits (CA and SPCC) were not examined in that study.…”
Section: Wtc Communication Traits and Ei In Language Learningmentioning
confidence: 82%
“…Students' oral proficiency is connected to students' willingness to communicate (WTC), teacher support, and unthreatening learning environment [30]. Literature supports that students' WTC in English in the classroom is positively associated with their proficiency of oral communication [32,81]. Teacher involvement and immediacy behaviors impact students' willingness toward classroom participation [26,44,57].…”
Section: Tendency Of Unwillingness To Communicatementioning
confidence: 99%
“…Though many variables might have a direct or indirect influence on L2 acquisition, a learner's attitude, motivation, and communication anxiety have a significant impact on his or her L2 oral proficiency [91]. Students' WTC is found to be a very influential factor on developing English oral proficiency [32,81].…”
Section: Affective Characteristics In L2 Acquisitionmentioning
confidence: 99%
“…Duygusal beceri eğitimi ve yabancı dil öğretimi kavramları arasındaki ilişkiyi inceleyen birçok araştırmada (Fahim ve Pishgadam, 2007;Ghanadi ve Ketabi, 2014;Jamshidifar, 2013;Öz, Demirezen ve Pourfeiz, 2015;Pishghadam, 2009;Rudolfova, 2015) duygusal becerileri yüksek öğrencilerin yabancı dil öğrenme ile ilgili tutumları ve başarılarının da yüksek olduğu varsayımı görülmektedir. Ayrıca araştırmacılar yabancı dil öğretiminin temelinin iletişim ve empati üzerine kurulu olan ve öğrenen için özellikle ilk zamanlarda kaygı ve endişe doğurucu bir dizi olumsuz hissi yaşamaya oldukça eğimli olduğu bir süreç olarak değerlendirmişlerdir.…”
unclassified